DEVELOPMENT OF STRATEGIES FOR INNOVATIVE DEVELOPMENTOF SMALL AND MEDIUM BUSINESS ENTERPRISES - NYZHNYK, O. (Herald of Khmelnytskyi National University. Economic sciences, 2021)
The analysis of modern models of innovative development of enterprises is carried out, the criteria of choice of model for enterprises of small and medium business of strategic innovative development of enterprises are chosen and the system model of innovative strategy of the enterprise is offered. The general model of innovation strategy of small and medium enterprises, generated by a system of diverse target functions in the modeling process, requires a series of stages that allow to solve a set of strategic tasks to optimize the process of innovation in the enterprise. The model of strategic innovative development of small and medium-sized enterprises is a multi-criteria task of simultaneous optimization of several target functions on a given set of innovative goals. Building a model requires the involvement of experts who could form the necessary directions of development of the object and identify a system of sub-goals of relevant innovation in each area or solve the problem of redistribution of innovation goals in already known areas of innovation as a strategic vision of management. In order to obtain adequate and complete results, it is necessary to make the correct choice of innovation goals, which would be fully included in the set of possible innovative transformations. Methodical providing of processes of formation of strategy modeling of innovative development of the enterprises of small and average business is formed by: the theory of graphs - construction of scenarios of realization of innovative processes and structure of innovative strategy; expert assessments - formation of necessary resources, selection of innovative goals, directions of innovative development, assessments of efficiency of innovative transformations; fuzzy set theory - analysis of the priority of innovation goals in conditions of uncertainty, structuring of innovation projects; theory of optimization methods - effective distribution of the supporting component according to the selected innovation goals, formation of the optimal structure of the innovation strategy.